Servicescape and Group References in Determining Hedonic Value and Its Implication on Impulsive Buying - Aa Willy Nugraha; Yusuf Abdullah (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
Consumer decision in purchasing product generally depend on his/her needs. The impulsive buying as the purchasing activity, in contrast, was based on the emotional encouragement. In the other hand, customer got pleasant experiences after purchasing that product spontaneously. That is a hedonic value which is customer circumstances encouraging buying decision. This study objectives were to know whether the servicescape and reference group could be determinant factors of hedonic value and impulsive buying activity in Plaza Asia Tasikmalaya. This study was quantitative research, a statistical datas based, with survey method approach. The data collected was by fulfiling questionnaire by respondent with convenience sampling technique. This sampling technique is a type of no-probability sampling method which the sample method is taken from a group of people easy to contact or reach. The literature studies also applied to enrich the explanation of the variables analyzed. The sample size was 300 visitors of Plaza Asia Tasikmalaya. The sample size was counted by 15 times of the number of observed variables. Then, the data was analyzed directly and indirectly using the Structural Equation Modeling (SEM) technique. This analysis technique was many advantages, were analyzing not only the latent variables but also its observed variables. The analysis was including normality testing, goodness of fit analysis. The result indicated that the determinant factors of hedonic value included servicescape and reference group were affected it signicifantly and had implication on impulse buying. Thus, the hedonic value of consumer in buying product in Plazaz Asia was affected partially and simultaniously by servicescape and reference group.